The Relationship Of Mother Characteristics And Family Support With The Event Of Post Partum Blues In Bpm Listiorini - Liya Lugita Sari; Taufianie Rossita; Yesi Putri (Institute of Computer Science (IOCS), 2022)
Postpartum blues is a condition of mood swings that have a mild effect starting in the first week after delivery and worsening on the third and fifth day and can last for 14 days after delivery. The incidence of postpartum blues is experienced by 80% of mothers or 4-5 new mothers, but the incidence of the baby blues itself has not been fully recorded. This study aims to determine the relationship between maternal characteristics and the incidence of postpartum blues in BM Listiorini, South Bengkulu Regency. This study uses analytical research with a correlation study approach (cross sectional). The population in this study were all postpartum mothers at BPM Listiorini in the month of visiting in January-February 2022. The sample used was a total sampling of 30 people. The analysis was carried out univariate and bivariate with Chi Square test. The results of the study of the relationship between maternal age and the incidence of postpartum blues (0.015 < 0.05), education with the incidence of postpartum blues (p 0.171 > 0.05), parity with the incidence of postpartum blues (0.002 < 0.05) Social support with incidence of postpartum Blues (0.002 < 0.05). From the research results, age, parity and social support have a relationship with the incidence of postpartum blues, while education has no relationship with the incidence of postpartum blues. It is necessary to increase knowledge in the form of counseling on preparation for parenthood and knowledge about the postpartum blues.